Nuclear topography and expression of the BCR/ABL fusion gene and its protein level influenced by cell differentiation and RNA interference - Bártová, Eva; Harnicarová, Andrea; Pacherník, Jirí; Kozubek, Stanislav (Leukemia research, 2005)
Nuclear topography, expression of the BCR/ABL fusion gene and its protein level/cellular pattern were studied in CML cell line K562 stimulated to differentiation, apoptosis and influenced by ABL-RNA interference (ABL-RNAi). Phorbol ester-induced maturation of K562 cells was accompanied by repositioning of down-regulated BCR/ABL genes closer to the nuclear membrane. This nuclear rearrangement could be connected with differentiation-related heterochromatinization of the amplified BCR-ABL locus, as demonstrated by increased histone H3(K9) dimethylation and decreased H3(K9) acetylation of B3A2 breakpoint. Topography of BCR/ABL in differentiated K562 cells was compared with other leukemic cell types: PMA-maturation of HL60 cells did not influence the nuclear positioning of individual BCR and ABL genes. Moreover, BCR and ABL genes in non-stimulated HL60 as well as in the bone marrow cells of CML patients, i.e. also BCR/ABL fusion genes, were positioned more interiorly in comparison with BCR/ABL multiple loci of K562 cells. Decreased expression of BCR/ABL gene was also found after cell stimulation by selectively pro-apoptotic agent etoposide and by ABL-RNAi leading to apoptosis. In order to compare the efficiency of selected experimental strategies, levels of Bcr/Abl and c-Abl proteins were determined and in all cases tested were reduced. In K562 cells the Bcr/Abl and c-Abl proteins were distributed homogeneously in both the cell nucleus and cytoplasm, while differentiation of K562 cells was characterized by a distinct pattern of Bcr/Abl and c-Abl proteins that were focally distributed rather in the cytoplasm while apoptotic population was completely absent of Bcr/Abl and c-Abl signals.
Keywords: down regulace; bcr-abl fúzní proteiny; tetradekanoylforbolacetát; RNA interference; Gene Expression Regulation, Leukemic; Fusion Proteins, bcr-abl; Tetradecanoylphorbol Acetate; Cell Nucleus; Cell Line, Tumor; antigeny povrchové; HL-60 buňky; chronická myeloidní leukemie; western blotting; buněčná diferenciace; molekulární sekvence - údaje; buněčné jádro; regulace genové exprese u leukemie; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Blotting, Western; buňky K562; Down-Regulation; lidé; HL-60 Cells; Humans; Antigens, Surface; apoptóza; K562 Cells; Molecular Sequence Data; nádorové buněčné linie; RNA Interference; Apoptosis; Cell Differentiation